ANALISIS LAPORAN KEUANGAN GUNA MENILAI KINERJA KEUANGAN PT CAMPINA ICE CREAM INDUSTRI TBK - Arofah, Anastasia; Nugroho Budi Wirawan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This study aims to describe the company's financial performance PT Campina Ice Cream Industri Tbk with liquidity ratio analysis. The research method uses a descriptive quantitative approach. Secondary quantitative data from the financial reports of PT Campina Ice Cream Industri Tbk for the 2018-2021 period. Data collection by literature study and documentation. The results showed that the financial performance of PT. Campina Ice Cream Industri Tbk as a whole on average from 2019-2021 in terms of the liquidity ratio, according to the current ratio and quick ratio calculations it is good because the resulting ratio is above 1. However, the cash ratio shows that it is not favorable because the ratio's result is too low—below 1—when viewed from this perspective.